Silicon Nanoparticles More Efficiently Alleviate Arsenate Toxicity than Silicon in Maize Cultiver and Hybrid Differing in Arsenate Tolerance - Tripathi, Durgesh Kumar; Singh, Swati; Singh, Vijay Pratap; Prasad, Sheo Mohan; Chauhan, Devendra Kumar; Dubey, Nawal Kishore (Frontiers in Environmental Science, 2016)
Though role of silicon (Si) in alleviation of various abiotic stresses is well known; however, role of silicon nanoparticles (SiNp) in mitigation of abiotic stresses is still not known. Therefore, hydroponic experiments were conducted to investigate if SiNPs are more effective than Si in mitigation of arsenate (AsV; 25 and 50 µM) toxicity in maize cultivar and hybrid differing in AsV tolerance. Under AsV stress, reduction in growth was accompanied by enhanced level of As and oxidative stress. AsV inhibited activities of antioxidant enzymes like ascorbate peroxidase, glutathione reductase and dehydroascorbate reductase (except superoxide dismutase). The redox status of ascorbate and glutathione was disturbed by AsV as indicated by a steep decline in their reduced/oxidized ratios. However, addition of Si and SiNp ameliorates AsV toxicity in maize. Si and SiNp both could reduce AsV toxicity in maize cultivar and hybrid, which could be related with decreased accumulation of As and oxidative stress, and enhanced components of the ascorbate-glutathione cycle (AsA-GSH cycle). But lowering in the accumulation of As and oxidative stress markers, and enhancement in components of the AsA-GSH cycle was prominent in SiNp fed seedlings under AsV stress. The results also showed that SiNp are more effective in reducing AsV toxicity than Si, which is due to their greater availability to seedlings. Comparing responses of cultivar and hybrid, maize cultivar shows more resistance against AsV than hybrid.